2013
DOI: 10.1186/1471-2180-13-287
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of N terminus of enterovirus 71 VP4 elicits cross-protective antibody responses

Abstract: BackgroundEnterovirus 71 (EV71) is major cause of hand, foot and mouth disease. Large epidemics of EV71 infection have been recently reported in the Asian-Pacific region. Currently, no vaccine is available to prevent EV71 infection.ResultsThe peptide (VP4N20) consisting of the first 20 amino acids at the N-terminal of VP4 of EV71 genotype C4 were fused to hepatitis B core (HBcAg) protein. Expression of fusion proteins in E. coli resulted in the formation of chimeric virus-like particles (VLPs). Mice immunized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Two other neutralizing epitopes were localized to VP2 residues 136-150 (known as VP2-28) [153] and VP3 residues 55-69, which form a 'knob' and are 100 % conserved across EV-A71 genotypes A, B1-B5 and C1-C4 [154]. One more epitope was localized to the I b-strand of VP1, two others were localized to the N-terminal loop of VP3 [155] and another one was localized within the N-terminal 20 amino acids of VP4 [156]. Mice immunized with corresponding peptides or with the epitope exposed on chimeric VLPs developed neutralizing responses to EV-A71.…”
Section: Neutralization Of Picornaviruses Neutralization Of Ev-a71 Anmentioning
confidence: 99%
“…Two other neutralizing epitopes were localized to VP2 residues 136-150 (known as VP2-28) [153] and VP3 residues 55-69, which form a 'knob' and are 100 % conserved across EV-A71 genotypes A, B1-B5 and C1-C4 [154]. One more epitope was localized to the I b-strand of VP1, two others were localized to the N-terminal loop of VP3 [155] and another one was localized within the N-terminal 20 amino acids of VP4 [156]. Mice immunized with corresponding peptides or with the epitope exposed on chimeric VLPs developed neutralizing responses to EV-A71.…”
Section: Neutralization Of Picornaviruses Neutralization Of Ev-a71 Anmentioning
confidence: 99%
“…Phage library construction: Six-week-old female BALB/c mice were immunized with an intraperitoneal injection of 5 mg recombinant chimeric particles composed of HBcAg and VP4N20 as described previously (22). The sequence of VP4N20 is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Immunization with the VP4 peptide elicits a broad neutralizing antibody response against various EV71 genotypes (22). In the present study, a phage display system was used to produce a recombinant mAb targeting this conserved peptide (designated VP4N20) of EV71 VP4.…”
Section: Ev71mentioning
confidence: 99%
See 1 more Smart Citation
“…14,[21][22][23][24] Recently, it was found that combined peptides in the VP2 protein domain could be effective in protecting against EV71, 25 and the VP4 N terminus can induce cross-protection against EV71. 26 These studies suggest that P1 protein is an ideal EV71 vaccine candidate. Human enterovirus 71 (eV71) plays an important role in hand, foot, and mouth disease (HFMD), which recently caused the death of hundreds of children in the Asia-Pacific region.…”
Section: Introductionmentioning
confidence: 99%